Occurrence of antibiotic and treatment performance of decentralized and conventional sewage treatment plants - Chen, Chee Xiang (2021)
Antibiotics are widely used in human society and have been frequently detected in sewage treatment plants (STP). However, the fate of antibiotics in these STPs is limited, particularly in Southeast Asian countries. Therefore, this study was conducted to evaluate the removal performances of six selected STPs on selected wastewater quality parameters and four frequently prescribed antibiotics (ampicillin, ciprofloxacin, erythromycin and sulfamethoxazole). The mass flow, mass balance and removal pathways analysis of the antibiotics in these STPs were conducted in detail. The insight into the relationship between the removals of wastewater quality parameters and antibiotics was provided. Sewage samples were taken at each stage of six STPs, comprising of two decentralised treatment plants (Imhoff tanks (IT)), four conventional treatment plants (three extended aerations (EA) and one conventional activated sludge (CAS)) in Johor Bahru district. Liquid and sludge samples were pretreated using solid phase extraction and ultrasonicate extraction, respectively, followed by their quantification using UHPLC-MS according to USEPA Method 1694. Quality control experiment was done for the selected antibiotics with internal surrogate standards. The findings showed that most of the conventional wastewater constituents were better removed in conventional treatment systems compared to decentralised treatment system. The findings revealed that ampicillin, ciprofloxacin, erythromycin and sulfamethoxazole were detected in most wastewater samples, including influent, secondary effluent, final effluent and sewage sludge samples. The antibiotic concentrations in the wastewater and sludge ranged from 4.2 ng/l to 2,690 ng/l and 1.7 ng/g to 317.4 ng/g, respectively. Between -26.4% to 99.9% of the antibiotics were removed in all STPs, depending on the process employed. A detailed antibiotic mass flow was conducted in EA and IT plants. An estimate of 45.6 g of ampicillin, 76.7 g of ciprofloxacin, 60.0 g of erythromycin and 225.4 g of sulfamethoxazole were discharged into the receiving river annually. The mass balance analysis indicated that biodegradation is the major route for the removal of all antibiotics studied. Sorption is only responsible for minor removal of ciprofloxacin, erythromycin and sulfamethoxazole. Statistical analysis showed that AMP and ERY removals were highly related with organic and solid removals while the removal of CIP and SMX were highly related with nutrient removal only. However, these relationships were insignificant due to small number of samples. As a conclusion, this study provided a preliminary evaluation on the removal of antibiotics in each stage of conventional and decentralised STPs. This work showed that conventional treatment system has better removal performance on wastewater quality parameters compared to decentralised treatment system. However, the removal of antibiotics accomplished by both conventional treatment systems is not significantly superior than that of decentralised treatment systems. Both systems are insufficient to prevent the discharge of antibiotics into the environment.